Temporal Trends and Variation in Early Scheduled Follow-Up After a Hospitalization for Heart Failure: Findings from Get With The Guidelines-Heart Failure. (January 2016) - DeVore, Adam D.; Cox, Margueritte; Eapen, Zubin J.; Yancy, Clyde W.; Bhatt, Deepak L.; Heidenreich, Paul A.; Peterson, Eric D.; Fonarow, Gregg C.; Hernandez, Adrian F.
Abstract : Background—: Previous data demonstrate early follow-up (ie, within 7 days of discharge) after a hospitalization for heart failure is associated with a lower risk of readmission, yet is uncommon and varies widely across hospitals. Limited data exist on whether the use of early follow-up after discharge has improved over time. Methods and Results—: We used data from Get With The Guidelines-Heart Failure (GWTG-HF) linked to Medicare claims to examine temporal trends in early follow-up and to assess for patient and hospital characteristics associated with early scheduled follow-up. In the overall GWTG-HF cohort, we studied 52 438 patients discharged from 239 hospitals from 2009 to 2012. Scheduled early follow-up at the time of hospital discharge rose from 51% to 65% over time ( P <0.001). After multivariable adjustment, patients with older age (odds ratio, 1.04; 95% confidence interval, 1.01–1.07), certain comorbidities (anemia, diabetes mellitus, and chronic kidney disease), and the use of anticoagulation at discharge (odds ratio, 1.16; 95% confidence interval, 1.11–1.22) were associated with greater likelihood for early scheduled follow-up. Patients treated in hospitals located in the Midwest (odds ratio, 0.67; 95% confidence interval, 0.50–0.91) were less likely to have early scheduled follow-up. In a subset of patients with linked Medicare claims, we observed smaller improvements in actual early follow-up visits over time from 26% to 30% ( P =0.005). Conclusions—: From 2009 to 2012, there was improvement in early scheduled outpatient follow-up and, in the subset analyzed, improvement in actual early follow-up visits for hospitalized patients with heart failure. However, substantial opportunities remain for improving heart failure transitional care. Abstract : Supplemental Digital Content is available in the text.